A Natural Jewel Threatened by Maritime Insecurity in the Gulf of Guinea - Musayyab, Said; Sutanto, Rudy; Susmoro, Harjo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Gulf of Guinea, an area rich in natural beauty and natural resources such as oil, gas, and fisheries, faces serious threats from widespread maritime piracy activities. The region is an important economic center, but maritime insecurity threatens its economic stability and development. Numerous regional and international initiatives have been undertaken to enhance security in these waterways, such as the Nigerian government's